Soothing something deeper still: Reflections on an academic development-student partnership - Cunningham, Catriona; Cunningham, Tom; Gardiner, Sarah; Caspary, Ida; O’Hara, Kathleen; Tanka, Fanni (International Journal for Students as Partners, 2022)
This case study critically reflects on the impact of the Students as Partners in Learning initiative at the University of Stirling. The authors (two academic developers and four students) explore collectively how our partnership enabled us to reimagine a shared understanding and common learning and teaching purpose among our staff and students. We draw playfully on the image of a river as our structure but also as a metaphor for our reflections. This case study aims to provide a reflective evaluation of the progress made, and lessons learnt, in this ongoing process of partnership through an open and honest conversational flow between each of the authors, opening up questions about where we go next that will undoubtedly resonate with our readers.